Prevalence of Spinal Segmental Sensitization Syndrome in Outpatients Attending Physical Medicine and Rehabilitation Centers for Chronic Musculoskeletal Pain: A Multicenter Study - Nakazato-Nakamine, Tomas; Romani, Franco; Gutierrez, Cesar; Quezada, Pablo; Vera, Ruth; Artica, Karina (Archives of physical medicine and rehabilitation, 2025)
To determine the prevalence of spinal segmental sensitization (SSS) syndrome, a regional pain disorder, among patients visiting physical medicine and rehabilitation centers (PM&RCs) for chronic musculoskeletal pain (CMSP). An observational, descriptive, cross-sectional study conducted from March to July 2023. Seven PM&RCs from 5 cities, representing 3 care systems: Social Security (SS), Ministry of Health (MH), and private practice (PP). All patients, regardless of age, attending a physiatry consultation for CMSP for the first time and who provided informed consent to participate were included. Nonprobabilistic sampling was employed. Not applicable. We estimated the overall prevalence of SSS syndrome as a percentage among patients with CMSP, stratified by health care institution, sex, age, and occupation type. We also recorded the spinal segments involved and any concomitant painful disorders (CPDs). SSS syndrome was diagnosed using standardized criteria. Of the eligible participants, 319 with CMSP were enrolled; 73.4% were women, and the median age of participants was 56.9 (range, 13-89y) years. The overall prevalence of SSS syndrome was 53.3%. Of these, 69.1%, 42.2%, and 13.8% were in the SS, MH, and PP systems, respectively. The most affected were female participants (56.4%), those aged 50-64 years (60.4%), and those with active jobs (58.8%). Most commonly, the lumbosacral and lumbar segments were affected, followed by the lower and middle cervical levels. Spine pathologies were the most common CPDs. The prevalence of SSS syndrome was high among patients who visited PM&RCs for CMSP and varied according to the care system. Further research on SSS syndrome is warranted to relieve the burden it poses on patients with CMSP and ensure proper diagnosis in clinical practice.